The Origins of the German Corporation – Finance, Ownership and Control - Franks, Julian; Mayer, Colin; Wagner, Hannes F. (Review of Finance, 2006)
Abstract The ownership of German corporations is quite different today from that of Anglo-American firms. How did this come about? To what extent is it attributable to regulation? A specially constructed data set on financing and ownership of German corporations from the end of the 19th century to the middle of the 20th century reveals that, as in the UK, there was a high degree of activity on German stock markets with firms issuing equity in preference to borrowing from banks, and insider and family ownership declining rapidly. However, unlike in the UK, other companies and banks emerged as the main holders of equity, with banks holding shares primarily as custodians of other investors rather than on their own account. The changing pattern of ownership concentration was therefore very different from that of the UK with regulation reinforcing the control that banks exercised on behalf of other investors.